2015
DOI: 10.3390/toxins7030755
|View full text |Cite
|
Sign up to set email alerts
|

Pokeweed Antiviral Protein: Its Cytotoxicity Mechanism and Applications in Plant Disease Resistance

Abstract: Pokeweed antiviral protein (PAP) is a 29 kDa type I ribosome inactivating protein (RIP) found in pokeweed plants. Pokeweed produces different forms of PAP. This review focuses on the spring form of PAP isolated from Phytolacca americana leaves. PAP exerts its cytotoxicity by removing a specific adenine from the α-sarcin/ricin loop of the large ribosomal RNA. Besides depurination of the rRNA, PAP has additional activities that contribute to its cytotoxicity. The mechanism of PAP cytotoxicity is summarized based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 97 publications
(133 reference statements)
0
24
0
Order By: Relevance
“…Interestingly, extracts from transgenic plants expressing PAPW237* protected tobacco plants from Potato Virus X infection, while the plant extracts from catalytic site mutant PAPE176V did not. PAP proteins have been studied since the nineties by the group headed by Tumer focusing on their potential applications to agriculture [ 38 ]. They also found that transgenic Arabidopsis (Line 512) plant expressing PAPW237* displayed an enhanced resistance to a strain of Tobacco Etch virus (TEV) and detected several genes upregulated, including auxin-responsive genes (more than 4-fold vs. basal), as well as genes involved in immunity and plant defense when performing a transcript profiling analysis using the Affymetrix Arabidopsis microarray.…”
Section: Biotechnological Application In Agriculturementioning
confidence: 99%
“…Interestingly, extracts from transgenic plants expressing PAPW237* protected tobacco plants from Potato Virus X infection, while the plant extracts from catalytic site mutant PAPE176V did not. PAP proteins have been studied since the nineties by the group headed by Tumer focusing on their potential applications to agriculture [ 38 ]. They also found that transgenic Arabidopsis (Line 512) plant expressing PAPW237* displayed an enhanced resistance to a strain of Tobacco Etch virus (TEV) and detected several genes upregulated, including auxin-responsive genes (more than 4-fold vs. basal), as well as genes involved in immunity and plant defense when performing a transcript profiling analysis using the Affymetrix Arabidopsis microarray.…”
Section: Biotechnological Application In Agriculturementioning
confidence: 99%
“…The RIPs are divided into three types based on their physical properties. Type 1 RIPs such as pokeweed antiviral protein (PAP), trichosanthin (TCS) and saporin are single chain, highly basic monomeric enzymes, approximately 30 kDa in size [ 19 , 20 , 21 ] Type 2 RIPs consist of an A chain and variable number of B chains. The A chain is the active chain, while the B chain can bind receptors on the surface of eukaryotic cells and mediate retrograde transport of the A-chain to the cytosol.…”
Section: Introductionmentioning
confidence: 99%
“…Transgenic plants expressing the ribosome inactivating protein pokeweed antiviral protein PAP from P. americana and its non-toxic mutants were resistant to fungal infection (Di and Tumer 2015).…”
Section: Ribosome-inactivating Proteinsmentioning
confidence: 99%